Athletes and adversities: athletic identity and emotional regulation in time of COVID-19 - Costa, S.; Santi, G.; Di Fronso, S.; Montesano, C.; Di Gruttola, F.; Ciofi, E. G.; Morgilli, L.; Bertollo, M. (Sport Sciences for Health, 2020)
Background: The COVID-19 pandemic impacted on the sporting field, with athletes constrained in home isolation without the possibility to train and compete in their usual environments. This situation has been investigated within the theoretical frameworks of athletic identity and cognitive emotion regulation. Objectives: The objectives of our investigation were to: (a) validate the athletic identity measurement scale (AIMS) for use in Italian language; and (b) explore differences by gender, typology of sport (individual vs. team), and competitive level (elite vs. non-elite) in athletic identity and in cognitive emotion regulation during the Covid-19 lockdown period. Methods: To achieve these objectives, the reliability and construct validity of the Italian version of the AIMS have been tested in Study 1. Multivariate and univariate analyses were run to evaluate differences between different groups of athletes in Study 2. Results: Results from Study 1 suggest a 3-factor higher order model of athletic identity. Results from Study 2 highlight that, during this lockdown period, elite athletes and team sports athletes show higher athletic identity. Cognitive emotion regulation strategies are different for gender and for competitive level. Finally, athletes with higher athletic identity tend to ruminate and catastrophize more. Conclusions: The present multi-study paper contributes to the theoretical field with a validated measure of athletic identity in Italian language. It also provides some practical implications that could apply in this situation of isolation and can be extended to cases such as those of injury or illness.